IMPLEMENTASI PENDIDIKAN AGAMA ISLAM DALAM MEMBANGUN NILAI-NILAI RELIGIUS PADA PESERTA DIDIK MI QUR’ANI AL BAHJAH BLITAR - Ainun Najib, Ainun Najib; Ali Ahmad Yenuri (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2025)
Religious values are fundamental in shaping students' character and behavior in daily life. Islamic religious education plays a strategic role in instilling these values, aiming not only to develop students' cognitive abilities but also to internalize faith, piety, and moral integrity. This study explores the implementation of religious values in Islamic education at Madrasah Ibtidaiyah Qur’ani Al-Bahjah Blitar. The findings reveal that religious education is effectively integrated through a conducive learning environment, exemplary behavior by educators, structured routines, and consistent religious practices. These efforts contribute significantly to the formation of students' religious character, discipline, and ethical conduct. The success of character development is strongly supported by the synergy among school leadership, teachers, parents, and the surrounding environment.